2019
DOI: 10.1111/ijlh.13086
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of thromboelastography and conventional clotting test values with severe bleeding in critically ill patients with coagulopathy: A prospective study

Abstract: Introduction This study aimed to ascertain the associations of thromboelastography (TEG®) and standard laboratory test (SLTs) values with the presence of bleeding in critically ill patients with known coagulopathy. Methods Three groups of coagulopathic patients with (a) hepatic failure, (b) postoperative period after prolonged cardiac surgery, and (c) complex abdominal surgery with sepsis were prospectively included in this study. On intensive care unit (ICU) admission, patients were stratified into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…INR is another crucial predictive factor in the machine learning model. Several studies [43,44] found septic patients with elevated INR and platelet count appeared to have a greater risk of death compared with those without coagulopathy. There is no doubt that age and metastatic cancer as basic demographic information could be included in the model which plays unfavorable effects for the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…INR is another crucial predictive factor in the machine learning model. Several studies [43,44] found septic patients with elevated INR and platelet count appeared to have a greater risk of death compared with those without coagulopathy. There is no doubt that age and metastatic cancer as basic demographic information could be included in the model which plays unfavorable effects for the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, R time and LY30 were determined in our analysis to be a non-significant predictor of DIC in sepsis patients. 7,11,15,17 Nevertheless, Panigada et al, 14 using a modified UK-TEG assay, revealed that LY30 was significantly increased in patients with severe sepsis-induced DIC and shock patients, and mortality was predicted by the degree of fibrinolysis impairment (OR 0.95, 95% CI, 0.93-0.98, P = .003). Significant correlations were observed between VHAs and conventional coagulation assays when used collectively to evaluate hemostasis in septic patients.…”
Section: Significance Statementmentioning
confidence: 99%
“…Interestingly, hypocoagulability or fibrinolysis in sepsis patients who eventually developed DIC was documented in all studies (822 patients). Hypocoagulability in sepsis patients was also found to be an independent predictor of shock, 5,7-10 DIC, 8,[11][12][13][14] hemorrhage, 15,16 organ failure, and/or mortality rate. 5,[9][10][11]14,[16][17][18][19] Few studies documented higher rates of DIC and mortality in patients who progress to a hypocoagulable state after admission.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Thromboelastography (TEG) is a routine test of coagulation that assesses the whole process of the clotting along time in the body [15], TEG provides a full-scale evaluation of clot formation, elasticity, and duration with measures describing various coagulation elements [16]. K-value (clotting time) re ects the rate of blood clot formation and is an indicator of brinogen function [17], Angle (α-angle) represents the clot growth rate, MA (maximum amplitude) means the maximum clot amplitude [18], A30 (amplitude at 30 min) measures clot strength at 30 minutes after MA [19], and TPI (thrombodynamic potential index) was derived from MA and K value [20]. TEG yields information about all phases of coagulation and provides further information over standard coagulation tests [16,21].…”
Section: Introductionmentioning
confidence: 99%